Association Between Dietary Patterns and Fluorosis in Guizhou, China - Liu, Jun; Yang, Sheng; Luo, Ming-jiang; Chen, Ting; Ma, Xiao-juan; Tao, Na; Zhao, Xun; Wang, Dong-hong (Frontiers in Nutrition, 2020)
OBJECTIVE: Many studies have explored the effects of individual foods or nutrients on fluorosis, but no studies focused on dietary patterns. This study examined the relationship between dietary patterns and coal-burning fluorosis in Guizhou, China. METHODS: This 1:1 matched case-control study was conducted in Zhijin County of Guizhou province with a sample of 200 cases of fluorosis and 200 age and gender matched controls. Habitual dietary intake was assessed by face-to-face interviews, using a validated 75-item food frequency questionnaire (FFQ) and various covariates using structured questionnaires. The dietary patterns were identified by factor analysis. RESULTS: The factor analysis identified three major dietary patterns: healthy, easy-to-roast and high protein. After adjusting for various confounders, a decreased risk for fluorosis was observed in the highest tertile of the healthy dietary pattern relative to the lowest tertile (OR=0.47, 95% CI = 0.27-0.84, P-trend=0.003) and a positive association was observed between the easy-to-roast dietary pattern and fluorosis risk (OR = 2.05, 95% CI=1.15-3.66), with a significant linear trend (P=0.017). No association with fluorosis risk was detected for the high protein pattern. The relationships remained significant when the analyses were stratified by gender and subtype of fluorosis. CONCLUSION: The healthy dietary pattern may lower coal-burning fluorosis risk; in contrast, the easy-to-roast pattern significantly increases the risk of coal-burning fluorosis.